Instrumen Survei Kepuasan Mahasiswa Berbasis Kriteria Unggul Lamemba: Pengembangan Dan Validasi - Wahyudi, Wahyudi; Arianto, Arianto; Mahyus, Mahyus; Zawitri, Sari (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2024)
This study aims to develop and test the validity and reliability of a student satisfaction survey instrument at Politeknik Negeri Pontianak, focusing on three main dimensions: Academic Services, Administrative Services, and Other Services. The analysis method employed is Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the relationships between items and the measured dimensions. The findings indicate that most items demonstrate good reliability, as shown by Cronbach’s Alpha values above 0.9 for all dimensions. However, issues with discriminant validity were identified, particularly in the Administrative Services dimension, which requires further review. Some items with low outer loading values are suggested for revision or removal. Additionally, model fit analysis results reveal that, although the model shows adequate performance, further improvements are necessary to enhance the overall model fit. This study makes an important contribution to the development of a more effective survey instrument for measuring student satisfaction while offering insights for educational institutions to enhance their services. The implications of this research suggest the need for continuous evaluation of the instrument and the use of larger samples in future studies to improve the generalizability of the findings. Keywords: Student Satisfaction Survey, Academic Services, Data Quality Testing, Construct Validation, PLS-SEM, Reliability, Validity.